2015
DOI: 10.1007/s00592-014-0711-y
|View full text |Cite
|
Sign up to set email alerts
|

Association between body mass index and diabetic retinopathy in Chinese patients with type 2 diabetes

Abstract: Overweight patients have lower DR prevalence than normal weight individuals, which may be attributable to better β cell function in overweight patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
30
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 42 publications
(72 reference statements)
5
30
1
Order By: Relevance
“…48 It may not be that higher BMI is protective towards DR, but that individuals with lower BMI may have more severe DM (as patients with decompensated disease may undergo a catabolic phase resulting in unintentional weight loss) and thus have a higher risk of developing DR. 48 Lu et al also attributed this inverse relationship to better pancreatic β-cell function in overweight individuals. 46 In contrast to our observation, however, studies in Turkey 23 and Australia 49 found obesity to be an independent risk factor for DR with persons with higher BMI being more likely to have DR and more severe stages of DR.…”
Section: Discussioncontrasting
confidence: 99%
“…48 It may not be that higher BMI is protective towards DR, but that individuals with lower BMI may have more severe DM (as patients with decompensated disease may undergo a catabolic phase resulting in unintentional weight loss) and thus have a higher risk of developing DR. 48 Lu et al also attributed this inverse relationship to better pancreatic β-cell function in overweight individuals. 46 In contrast to our observation, however, studies in Turkey 23 and Australia 49 found obesity to be an independent risk factor for DR with persons with higher BMI being more likely to have DR and more severe stages of DR.…”
Section: Discussioncontrasting
confidence: 99%
“…43 Morbid obesity may be an influencing factor of chronic kidney disease (CKD) in women. 44 A U-shaped association between BMI and DR in Chinese T2DM patients was found by Lu et al 45 A central-based, cross-sectional study containing 518 DM patients showed the relationship between DR and BMI in adult patients with T2DM. The correlation study between DR and BMI found that BMI had an inverse relationship with DR when BMI was deemed a continuous variable (p = 0.009 and correlation coefficient 0.467).…”
Section: Body Mass Index and Triglyceridesmentioning
confidence: 87%
“…It has been suggested that the effect of obesity might be different according to the type of DM . In type 1 DM, obesity and abdominal obesity have been found to be risk factors for developing diabetic retinopathy, whereas two cross‐sectional studies of type 2 DM found less retinopathy in overweight and obese subjects . In the latter study, the greater risk in underweight subjects was no longer significant after adjustment for fasting c‐peptide, the authors hypothesizing that insulin deficiency may mediate retinal deterioration .…”
Section: Discussionmentioning
confidence: 99%